Nurse PerformanceThrough Motivation and Work Discipline on Productivity (Case at a Hospital in DKI Jakarta) - Cicih Ratnasih; Bambang Bernanthos; Syaiful; Angga Kurniawan (Yayasan Putra Adi Dharma, 2023)
This study examines the influence of factors related to the performance of hospital nurses in DKI Jakarta. These factors include motivation, work discipline which then in this study functioned as an independent variable and productivity as an intervening variable that affects the performance of nurses who functioned as a dependent variable. This research was conducted by quantitative research methods. This research was conducted by hospitals in DKI Jakarta in August – December 2022. The population in this study was hospital nurses in DKI Jakarta as many as 400 respondents. The instrument in this study is a questionnaire consisting of 40 questions. Based on the results of research from 400 respondents there is a direct and significant influence between motivation and work productivity which is 3,847%, there is a direct and significant influence relationship between work discipline and productivity which is 8,936%, there is a direct and significant influence between motivation and nurse performance which is 4,599%, there is a direct and significant relationship between work discipline and nurse performance which is 8,936%, There is a significant relationship between productivity and nurse performance which is 13.834%, there is a direct and significant influence between motivation and productivity through nurse performance which is 2.340%, %, there is a direct and significant influence between discipline and productivity through nurse performance which is 2.641%.